Relationship between soil properties and natural grassland vegetation on sodic soils - Szabó, András; Tóth, Tibor (Ecological Questions, 2011)
Salinity, pH, climate, and moisture content, along with topographical data were compared between plant associations, to define key factors affecting soil salt accumulation and establishment of natural vegetation. The extreme values found in some associations are explained by the spatial distribution of the studied points.